2021
DOI: 10.5539/jas.v13n9p27
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Concentration of Pyriproxyfen Reduces Testicular Connective Tissue Thickness in Euschistus heros Fabr. (Hemiptera: Pentatomidae)

Abstract: The aim of this study was to determine the effect of the insecticide pyriproxyfen (Tiger™ 100 CE), juvenile hormone analogue, when applied in a sublethal LC30 concentration (0.668 mL a. i. L-1), on the morphological and morphometric parameters of external and internal connective tissue (CT) of the Neotropical-brown stink bug Euschistus heros testicles. The insecticide was applied on nymphs from the 4th instar using a Potter tower with a working pressure of 82.73 kPa (12 lb pol-²) and 1 mL of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Insecticides belonging to the chemical group of benzoylureas are considered inhibitors of chitin synthesis and act on the ecdysis process during the immature phase of lepidopterans, when they prevent the secretion of a new cuticle and exocuticle release in the caterpillars, thus causing their mortality (Aliabadi et al, 2016). Similar results were observed in this work for the nymph ecdysis process, mortality, deformations, changes in the number of ovipositions, egg viability, in E. heros nymphs, although these insects are in a different order (Matsumoto et al, 2021;Cremonez et al, 2019). In a study with the insecticides lufenuron (0.187 g a.i.…”
Section: Discussionsupporting
confidence: 82%
“…Insecticides belonging to the chemical group of benzoylureas are considered inhibitors of chitin synthesis and act on the ecdysis process during the immature phase of lepidopterans, when they prevent the secretion of a new cuticle and exocuticle release in the caterpillars, thus causing their mortality (Aliabadi et al, 2016). Similar results were observed in this work for the nymph ecdysis process, mortality, deformations, changes in the number of ovipositions, egg viability, in E. heros nymphs, although these insects are in a different order (Matsumoto et al, 2021;Cremonez et al, 2019). In a study with the insecticides lufenuron (0.187 g a.i.…”
Section: Discussionsupporting
confidence: 82%
“…In E. heros, pyriproxyfen may cause a hormonal imbalance in nymphs that alters their normal development, preventing adult formation. In other studies, pyriproxyfen did affect the development of the gonads of male adults when applied over late instar nymphs (Matsumoto et al, 2021). Studies conducted by Rill, Grafton-Cardwell, and Morse (2007) showed that with the increase in pyriproxyfen concentration, there was an increase in the mortality of the early nymphal stages of the citrus plague Aonidiella aurantia Maskell (Hemiptera: Diaspididae).…”
Section: Resultsmentioning
confidence: 88%
“…Chitin biosynthesis inhibitors (CBIs) disrupt the normal development of nymphs of pentatomids (Bagheri et al, 2011;Cremonez et al, 2019;Roggia et al, 2011). Another insect growth disruptor, pyriproxyfen, acts as a juvenile hormone (JH) analog, affecting the normal development of late nymphal stages (Cremonez et al, 2017;Matsumoto et al, 2021). Studies carried out by these researches showed that both group of insecticides caused deformations in the external and internal anatomy of stink bugs, but they do not mention changes in the mouthparts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is known that pyriproxyfen has a negative effect on reproductive parameters (fecundity, fertility, and nymph viability) in females of the pentatomid Nezara viridula (Agüero et al, 2014), as well as decreased fecundity and fertility in E. heros observed soybean. It should be acknowledged that these soybean fields were treated with rates recommended for controlling the whitefly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) (Matsumoto et al, 2021). The interactions are similar and the site of action of JH, as well as its precursors and analogues, are the intracellular receptors of the basic Helix-Loop-Helix/Per-ARNT-SIM (bHLH-PAS) type, such as Met and Gce (Charles et al, 2011;Jindra et al, 2015).…”
Section: Fecundity and Fertilitymentioning
confidence: 99%